EVALUATION OF TWO COMMERCIAL VACCINES CONTAINING THE ANTIGEN-ANTIBODY COMPLEX AGAINST THE INFECTIOUS BURSAL DISEASE IN BROILERS - Vidal A., Karina (2009)
The present study evaluated the conferred protection by two immune complex (Icx) vaccines containing a 2512 strain of Infectious Bursa Disease virus (IBDV) linked to a virus specific antibodies. Groups A and B were subcutaneously vaccinated at one day old using two commercial Icx vaccines; Group C was submitted to the traditional vaccination programme using intermediate vaccines at 10 and 18 days of age; and Group D (control) remained without vaccination. At 35 days of age, 45 birds of each group were challenged with a standard IBDV strain F52/70. At days 4, 7, and 10 post challenge, 15 birds of each group were slaughtered for the evaluation of pathological lesions. Protection was measured through clinical signs, bursal index (BI), gross and microscopic lesions, serology, and productive parameters after challenge. Birds of all groups presented depression and diarrhoea, especially in group D. Bursal oedema was observed in all groups until day 10 day post challenge. The BI in the four groups revealed bursal atrophy but the histopathology lesions were more severe in the control group. Seroconversion was observed at the end of the study in groups with Icx vaccines (A y B). Productive parameters of the vaccinated groups were slightly better in vaccinated groups. Although the results indicated that the vaccinated groups were better protected compared with control group, the differences were not statistically significant.